Importance of measuring relationship quality in the retail industry: an asian perspective - Aziz, Md. Tareque (© 2012 ELK ASIA PACIFIC JOURNAL OF MARKETING AND RETAIL MANAGEMENT, 2016)
This article was published in ELK ASIA PACIFIC JOURNAL OF MARKETING AND RETAIL MANAGEMENT [© 2012 ELK's International Journal of Marketing] and the definite version is available at : http://www.elkjournals.com/MasterAdmin/UploadFolder/4-IMPORTANCE-OF-MEASURING-RELATIONSHIP/4-IMPORTANCE-OF-MEASURING-RELATIONSHIP.pdf The article website is at: http://www.elkjournals.com/